Incidência, Prevalência e Fatores Associados às Úlceras por Pressão em Unidade de Terapia Intensiva. - Silva, Maria do Livramento Neves (2013)
Introduction: The vulnerability of patients hospitalized in an intensive care environmental makes them more inclined toward to the risk of developing pressure ulcers than those ones that are in other wings of the same institution. Objectives: Analyze the incidence, prevalence and factors associated with pressure ulcers in an intensive care unit; Check the risk of developing PU in patients, using the Braden Scale; analyze the risk scores association of the Braden subscales with the development of pressure ulcers and verify the association of socio-demographic and clinical data and the risk factors with the pressure ulcers development. Method: This is a descriptive study, prospective, performed in an intensive care unit of a public hospital in João Pessoa. The study population consisted of all patients admitted during the period from July 17 to October 17, 2012. The sample was composed by 45 patients who fulfilled the inclusion criteria established. The study has been approved by the Ethics Committee of the UFPB Health Sciences Center, under protocol 0237/12. Data were collected through physical examination of patients by application of the Braden scale and by reviewing the medical files. Results: of 45 patients followed in the study 09 were already admitted with the injury and 08 developed during ICU stay, corresponding to an incidence of 8 (22.2%) and the prevalence of 17 (37.8%). In the prevalence it was verified the predominance of males, white and over the age of 70 years. The incidence recorded 4 (50%) for each gender, 5 (62.5%) for whites and 4 (50%) aged until 50 years. Regarding the identified baseline diseases has been observed the presence of one or more diseases in 75% of patients, being the most prevalent in the group with PU stroke 3 (100%) and COPD 5 (60%). In this same group 6 (54.5%) made use of corticoids, 13 (43.3%) of antibiotics and 6 (40%) receiving intravenous drugs. Regarding patients' physical examination with PU 9 (52.9%) were sedated, 12 (70.6%) connected to mechanical ventilation, 9 (52.9%) with thin or delicate skin and 9 (52.9%) with decreased turgor and elasticity. The hospitalization period varied from 5 to 48days in patients without PU and from 5 to 39in those who had presented the injury. Regarding the elapsed time for the development of injury 7 (87.5%) of cases occurred up to 10 days. Concerning the risk PU through the Braden Scale, was observed that 30 (66.6%) of the patients were classified as high risk, and those with PU 15 (88.2%) with the categories activity (bedridden) and friction and shear (problem) as Braden subscales most affected in this group. Conclusion: The incidence and prevalence of PU identified in the study are similar to the reality described in some scenarios of intensive care units in Brazil, but depicting an incidence rate lower than that found in most studies in the same population. It is suggested to invest in job training through continuing education in service and building and deploying protocols for prevention and treatment of these injuries.